2019
DOI: 10.5535/arm.2019.43.4.465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-training and Post-training Nordic Exercise on Hamstring Injury Prevention, Recurrence, and Severity in Soccer Players

Abstract: Hamstring strain injury is the most common noncon-tact muscle injury for soccer players, representing twothirds of thigh muscle strains [1]. Hamstring strain injury and recurrence rate were high in the past three decades.Objective To investigate the effect of adding Nordic exercise as post-training in decreasing hamstring initial, recurrent injuries rates, and their severity. Methods In this randomly controlled trial study, 34 professional football players aged 21 to 35 years were randomly assigned into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
27

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 21 publications
0
16
0
27
Order By: Relevance
“…However, both studies showed a very satisfactory effectiveness of the FIFA 11+ protocol. In the study by Elerian et al study [62], IRR achieved a rate of 0.256, but two different interventions were examined and compared in the study: Intervention Group 1 had the lowest IRR of all interventions at a computed rate of 0.1025. Both groups performing the eccentric exercise and Nordic hamstring exercise (NHE) had fewer injuries than the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both studies showed a very satisfactory effectiveness of the FIFA 11+ protocol. In the study by Elerian et al study [62], IRR achieved a rate of 0.256, but two different interventions were examined and compared in the study: Intervention Group 1 had the lowest IRR of all interventions at a computed rate of 0.1025. Both groups performing the eccentric exercise and Nordic hamstring exercise (NHE) had fewer injuries than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 517 players (Elerian et al [62], Espinosa et al [65], Petersen et al [64]) performed eccentric exercise as a preventive strategy. Among them, 495 players had this session before training, while 22 players had sessions both before and after training, with a greater focus on the Nordic hamstring exercise (NHE).…”
Section: Prevention Protocolsmentioning
confidence: 99%
“…Considerando que os testes funcionais aplicados no presente estudo são comumente usados como forma de triagem para identificar atletas com maior risco de lesão (GOOSSENS et al, 2015), posto que avaliam deficiências na função muscular (ERICSSON;DAHLBERG;ROOS, 2009), o presente trabalho trouxe resultados positivos da prática de um programa de prevenção de lesão sobre variáveis de desempenho funcional de membros inferiores em jovens atletas de handebol feminino. Sugere-se que a melhora obtida possa prevenir lesões futuras nessas atletas, uma vez que trabalhos ressaltam a eficácia da maioria dos exercícios utilizados neste estudo para a prevenção de lesão de membros inferiores em atletas (MAZUREK et al, 2018;SILVERS-GRANELLI et al, 2017;ELERIAN;EL--SAYYAD;DORGHAM, 2019;THOMPSON et al, 2017;WHITEHEAD et al, 2018;EUN-KYUNG, 2016).…”
Section: Discussionunclassified
“…Despite this information, eccentric actions have been emphasized by many programs for reducing injury risk of the hamstrings (van der Horst et al, 2015;Almeida et al, 2018;Elerian et al, 2019). Perhaps athletes with greater percentage of type II fibers should follow a more careful monitoring of the eccentric work they perform.…”
Section: Muscle Fiber Typementioning
confidence: 99%
“…Type II muscle fibers are more easily fatigued than type I fibers ( Lievens et al, 2020 ), and more susceptible to plyometric- ( Macaluso et al, 2012 ) as well as eccentric-induced muscle damage ( Fridén et al, 1983 ). Despite this information, eccentric actions have been emphasized by many programs for reducing injury risk of the hamstrings ( van der Horst et al, 2015 ; Almeida et al, 2018 ; Elerian et al, 2019 ). Perhaps athletes with greater percentage of type II fibers should follow a more careful monitoring of the eccentric work they perform.…”
Section: Part 2: Anatomic and Physiologic Variations Of The Hamstrings And Potential Implications For Injury Riskmentioning
confidence: 99%